PRELIMINARY STUDY ON MINOR ACTINIDE INCINERATION IN RSG-GAS WITHOUT ISOTOPE SEPARATION - R. Andika Putra Dwijayanto; Muhammad Alfarisie (Website, 2021)
Minor actinides (MA) resulted from nuclear power plants is often considered as nuisance in spent fuel management due to its considerably long half-life. One of available strategies to deal with MA is to incinerate it, in order to reduce its radioactivity. This paper presents a study on MA incineration in RSG-GAS research reactor. Unlike previous study, this work did not separate the MA into individual isotopes, but incinerated as a whole. ORIGEN2.1 code is employed to calculate MA incineration within RSG-GAS core. MA composition used in this study consists of Np, Am, and Cm isotopes. The Central Irradiation Position (CIP) of RSG-GAS is loaded by 6 kg of MA and irradiated for two years. The result shows that about 1 kg of MA were incinerated after two years of irradiation, or 18,87% of the initial concentration. However, the increase of Cm-242 isotope, along with newly-formed Pu isotopes, were found to be significantly increasing short-term radioactivity compared to un-irradiated MA. Thus, two years-worth of MA incineration cannot be considered as effective, and other strategies must be pursued.